Study of Residual Stress Relaxation Mechanics Using a Micro-indent Method - Díaz, F.V (2016)
The aim of this study is to show the feasibility and accuracy of a micro-indent method to comprehensively evaluate the relaxation mechanics of residual stress in specimens of rolled aluminium alloy. This micro-indent method was adapted to implement four annealing treatments. The residual displacements were measured using a high-accuracy measuring machine, which enables to decrease the absolute error down to ±300 nm. This study presents an innovative data analysis using Mohr's circles, which allowed to study all directions of the inplane residual stress for different relaxation times. The results revealed that the relaxation process finishes when the residual stress relief is completed in some preferential directions and then, a brief stress recovery phase begins.